2020
DOI: 10.1101/2020.03.31.017459
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

In silicoapproach for designing of a multi-epitope based vaccine against novel Coronavirus (SARS-COV-2)

Abstract: A novel Coronavirus (SARS-COV-2) has now become a global pandemic. Considering the severity of infection and the associated mortalities, there is an urgent need to develop an effective preventive measure against this virus. In this study, we have designed a novel vaccine construct using computational strategies. Spike (S) glycoprotein is the major antigenic component that trigger the host immune responses. Detailed investigation of S protein with various immunoinformatics tools enabled us to identify 5 MHC I a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 27 publications
(25 reference statements)
0
22
0
Order By: Relevance
“…At the same time, significant progress towards the isolation and design of vaccines (mRNA-1273 vaccine © 2020 Moderna, Inc) and neutralizing antibodies 9 has been made. A computational study identified the structural basis for multi-epitope vaccines 10,11 whereas in another study, the glycosylation patterns of the spike SARS-CoV-2 protein were computationally deduced 12 . In one study 13 , fully human single domain anti-SARS-CoV-2 antibodies with sub-nanomolar affinities were identified from a phage-displayed single-domain antibody library by grafting naïve CDRs into framework regions of an identified human germline IGHV allele using SARS-CoV-2 RBD and S1 protein as antigens.…”
Section: Mainmentioning
confidence: 99%
“…At the same time, significant progress towards the isolation and design of vaccines (mRNA-1273 vaccine © 2020 Moderna, Inc) and neutralizing antibodies 9 has been made. A computational study identified the structural basis for multi-epitope vaccines 10,11 whereas in another study, the glycosylation patterns of the spike SARS-CoV-2 protein were computationally deduced 12 . In one study 13 , fully human single domain anti-SARS-CoV-2 antibodies with sub-nanomolar affinities were identified from a phage-displayed single-domain antibody library by grafting naïve CDRs into framework regions of an identified human germline IGHV allele using SARS-CoV-2 RBD and S1 protein as antigens.…”
Section: Mainmentioning
confidence: 99%
“…All the three CTL and two HTL MPVs were fitting into the ectodomain region of TLR3 receptor (Figure 7). T cell immune response driving long-term robust adaptive immunity in the vast majority of the population (Abdelmageed et al, 2020;Ahmed et al, 2020;Akhand et al, 2020;An et al, 2000;Banerjee et al, 2020;Baruah et al, 2020;Bhattacharya et al, 2020;Fast et al, 2020;Gragert et al, 2013;Gupta et al, 2020;Herst et al, 2020;Ismail et al, 2020;Khan et al, 2020;Lee et al, 2020;Liu et al, 2020;Lu et al, 2014;Mitra et al, 2020;Nerli et al, 2020;Poran et al, 2020;Ramaiah et al, 2020;Saha et al, 2020;Sheikhshahrokh et al, 2020;Singh et al, 2020;Srivastava et al, 2020a;Srivastava et al, 2020b;ul Qamar et al, 2020;Vashi et al, 2020;Yazdani et al, 2020). Numerous highly antigenic regions have also been reported from SARS-CoV-2 proteins which have been recognized on the basis of large population coverage by favorable binding with large number of HLA allele distributed amongst different ethnic human population worldwide (Grifoni et al, 2020b;Yarmarkovich and Warrington et al, 2020).…”
Section: Screening Of Potential Epitopes From Sars-cov-2 Proteomementioning
confidence: 99%
“…Several recent articles have suggested that SARS-CoV-2 proteome fragments are important to the viral lifecycle, several of which are conserved in the Coronaviridae family and which are possible targets as epitopes [15][16][17][18][19][20][21][22] . This is of importance since the choice of attack points is crucial to the success of the therapy (drug design) or prevention (vaccine design).…”
Section: Introductionmentioning
confidence: 99%